NEURO-HUMORAL DISTURBANCES AND THEIR CORRECTION IN PATIENTS WITH MYOCARDIAL INFARCTION - V. A. Kokorin; N. A. Volov; A. V. Dudareva; N. V. Sytnik; Gen Hayshu (Российский кардиологический журнал, 2009)
.